Fabrication of functionalised-MWCNTS/metal chalcogenides composite non-enzymatic electrochemical sensor for the the detection of glucose - Maphake, Precious (My University, 2024)
One of the most significant analysis in medical diagnosis is blood glucose measurement. In other scientific and industrial domains, such as environmental monitoring, pharmaceuticals, and the food sector, they are equally indispensable, however commercial glucometers that are sold on the market frequently have a lot of flaws and limits. These can be caused by a variety of challenges, such as poor material design, incorrect storage, coding mistakes, issues with device calibration, manufacturing processes, and the substantial influence of ambient elements like pH and temperature. Some of these issues might be resolved by creating brand-new hybrid materials with enhanced characteristics (such stability and adsorption capabilities). The metal sulfide-decorated-functionalised-multi-walled carbon nanotube modified non-enzymatic glucose detecting sensor was studied. Many physicochemical and structural investigations, such as Fourier transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and Raman spectroscopy, were performed to characterize the synthesized nanocomposites. Electrochemical methods such as square wave voltammetry, cyclic voltammetry, and electrochemical impedance spectroscopy were used to comprehensively test the produced sensors. The p-MWCNTs were purified and functionalised by acid treatment into COOH-MWCNTs. Amine functionalise MWCNTs (NH2-MWCNTs) were donated by Mintek. Metal sulfides nanoparticles (FeS2 and ZnS) were synthesised using hydrothermal method under the same experimental conditions as the metal sulfides/f-MWCNTs nanocomposites for comparison in the electrochemical studies. Fourier transform infrared spectroscopy (FTIR) verified that carboxyl (COOH) and amine (NH2) functional groups were detected on the surface of the f-MWCNTs, which appeared at lower wavenumbers, i.e., below the fingerprint due to the presence of metal sulfides. Transmission electron microscopy (TEM) was used to confirm that FeS2 and ZnS nanoparticles successfully decorated MWCNTs in situ. The functionalized MWCNTs surface exhibited a well-dispersed distribution of metal sulfides, as demonstrated by TEM pictures. X-ray diffraction (XRD) was used to confirm the chemical composition of the as-prepared MWCNTs, indicating the existence of MWCNTs and metal sulfides. The XRD pattern of FeS2/COOH-MWCNTs nanocomposites represented crystal planes of pyrite FeS2. The ZnS/COOH-MWCNTs nanocomposites' XRD pattern agrees with published data and confirms that ZnS forms in the cubic (sphalerite) phase with acceptable crystallinity. The Raman spectra of pristine MWCNTs, COOH-MWCNTs, FeS2/COOH-MWCNTs, FeS2/NH2-MWCNTs ZnS/COOH-MWCNTs and ZnS/NH2-MWCNTs all showed three vibration bands namely, D, G, and G’, further confirming the presence of the carbonous nature of the MWCNTs. The electrochemical characteristics of the nanocomposites formed by metal sulfides/functionalized-MWCNTs were investigated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). These analyses were performed in a solution containing 5 mM K3Fe(CN)6 /K4Fe(CN)6 as the redox probe and 0.1 M KCl as the supporting electrolyte. The resultant nanomaterials had redox active groups that produced a signal on the electrode surface, and these groups could be used to build electrochemical sensors and biosensors. The cyclic voltammograms illustrate the comparative current in this decreasing order: ZnS/COOH-MWCNTs-GCE> FeS2-GCE> p-MWCNTs-GCE> BARE-GCE> ZnS/NH2-MWCNTs-GCE> FeS2/NH2-MWCNTs-GCE> GCE-ZnS-GCE˃ GCE-COOH-MWCNTs-GCE> FeS2/COOH-MWCNTs-GCE˃ NH2-MWCNTs-GCE. The fitted impedance data reveals that the GCE-ZnS/COOH-MWCNTs electrode has the lowest Rct value of 33 Ω, proposing a swift electron transfer of the GCE-ZnS/COOH-MWCNTs electrode as in comparison to the remaining electrodes, consistent with the findings from cyclic voltammetry. Consequently, the ZnS/COOH-MWCNTs nanocomposite showed better electroactivity and great potential to be employed for glucose detection. Square wave voltammetry (SWV) was used for the electroanalysis of the analyte (glucose) at the GCE-ZnS/COOH-MWCNTs. The results showed that the GCE-ZnS/COOH-MWCNTs had better electrocatalytic behaviour resulting from the higher oxidation peak currents (Ipa) and faster electron transport. The results from scan rate studies demonstrate that the scan rate (v) correlates directly with the glucose anodic current responses (Ipa) at GCE-ZnS/COOH-MWCNTs. The glucose oxidation mechanism at GCE-ZnS/COOH-MWCNTs was diffusion-controlled, indicated by the linear relationship observed between oxidation peak currents (Ipa) and the square root of the scan rate (v1/2). Employing square wave voltammetry, a limit of detection (LoD) of 0.83 mM was achieved for GCE-ZnS/COOH-MWCNTs within alinear dynamic range (LDR) of 1-9 mM. The sensitivity of the sensor was measured at 7.2 x 106 A.mM-1.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2024
Keywords: Linear dynamic range; Glucose oxidation mechanism; Cyclic voltammetry; Nanocomposites; Electrochemical; Spectroscopy; Voltammetry; Functionalise MWCNTs; Fabrication; Technology; Materials science; Fourier transform infrared spectroscopy; Blood glucose; Chalcogenides; Blood glucose monitoring; Blood glucose -- Analysis